2018
DOI: 10.1126/science.aao1503
|View full text |Cite
|
Sign up to set email alerts
|

CX3CR1 + mononuclear phagocytes control immunity to intestinal fungi

Abstract: Intestinal fungi are an important component of the microbiota, and recent studies have unveiled their potential in modulating host immune homeostasis and inflammatory disease. Nonetheless, the mechanisms governing immunity to gut mycobiota remain unknown. We identified CX3CR1+ mononuclear phagocytes (MNPs) as essential for the initiation of innate and adaptive immune responses to intestinal fungi. CX3CR1+ MNPs express antifungal receptors and activate antifungal responses in a Syk dependent manner. Genetic abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
226
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 237 publications
(235 citation statements)
references
References 51 publications
7
226
1
1
Order By: Relevance
“…However, the potential mechanisms through which immune cells recognize fungal dysbiosis-derived signals to regulate distal allergic airway immune responses remain poorly characterized. We have recently shown that CX3CR1 + MNPs that express several antifungal receptors can efficiently recognize and uptake gut commensal fungi (Cook and MacDonald, 2016; Leonardi et al, 2018). Therefore, we next hypothesized that the direct sensing of fungi by gut CX3CR1 + MNPs might be responsible for the distal effects of fungal dysbiosis on systemic immunity and lung airway inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the potential mechanisms through which immune cells recognize fungal dysbiosis-derived signals to regulate distal allergic airway immune responses remain poorly characterized. We have recently shown that CX3CR1 + MNPs that express several antifungal receptors can efficiently recognize and uptake gut commensal fungi (Cook and MacDonald, 2016; Leonardi et al, 2018). Therefore, we next hypothesized that the direct sensing of fungi by gut CX3CR1 + MNPs might be responsible for the distal effects of fungal dysbiosis on systemic immunity and lung airway inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Gut-resident CX3CR1 + MNPs play a critical role in regulation of intestinal immune response to bacteria and fungi under homeostatic and dysbiotic conditions (Diehl et al, 2013; Kim et al, 2018; Leonardi et al, 2018; Panea et al, 2015). Although fluconazole treatment contributed to increases of CD4 + T cell frequencies in the lung of HDM-immunized mice, we did not observe changes in CX3CR1 + MNPs frequencies in the lung of those mice (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, CX 3 CR1+ cells have been shown to directly transfer antigens to CD103+ DCs via gap junctions to induce tolerance [161]. A recent study has identified that CX 3 CR1+ mononuclear phagocytes are essential for the initiation of innate and adaptive immune responses to intestinal fungi in the colon and mesenteric lymph nodes but not the small intestine, and genetic ablation of CX 3 CR1+ cells in mice led to changes in gut fungal communities and the development of severe colitis [162]. …”
Section: Mycobiomementioning
confidence: 99%